Mineral-dependent physicochemical regimes govern the adsorption of soil viral communities - Meiyi Wang; Yongfeng Wang; Weipeng Liu; Zhibo Cheng; Xinyao Yang; Xiaolong Liang (Applied Soil Ecology, 2026)

Prediction of deep rock drilling resistance by integrating fractal theory and logging data: the Kuqa Depression block in the Tarim Basin - Yapeng Liu; Huan Zhao; Bo Wang; Tianyu Yang; Lei Yang; Shouhua Zhang; Ullah Zain; Wei Li (Acta Geophysica, 2026)

Interactions Between Crabs and the Environment: Progress and Prospects From a Behavioral Perspective - Boshan Zhu; Dapeng Liu; Fang Wang (Reviews in Aquaculture, 2026)
As ecosystem engineers, crab behaviors not only reflect the physiological state and welfare of individuals but also act as regulators influencing the function and stability of aquaculture systems. However, research on the behavioral responses of cultured crabs to environmental factors remains incomplete, and studies on how their behaviors affect the environment are even more limited. To enhance productivity, welfare, and environmental sustainability and provide theoretical support for the optimization of crab culture systems, it is essential to clarify the interactions between the behavior of crabs and the environmental factors. This review synthesizes and summarizes the major environmental factors, physical (temperature, substrate and shelter, sound, hydrostatic pressure), chemical (dissolved oxygen, ammonia, pH, pollutants, salinity), and biological (prey, conspecifics, polyculture species, pathogens), and their impacts on various behavioral patterns of crabs, including feeding, foraging, grooming, mating, aggressive, territorial, burying, burrowing, sheltering behavior, and cannibalism. Decoding sensory processing and behavioral mechanisms in crabs is pivotal for breakthroughs in intelligent and welfare‐oriented crab culture. Additionally, we summarize the disturbances caused by crab behaviors—such as burrowing, feeding, and social interactions—on substrate water characteristics, microbial composition, and polyculture species. Based on these insights, we list future research and applications in crab behavior, including precise behavioral monitoring, group behavior evaluation, and aquaculture environmental management. We hope this review will encourage greater attention to the behavior of cultured animals, promoting the application of behavioral studies in crab culture and providing theoretical support for the industry's high‐quality development.

Poplar–wheat intercropping and fertilizer application significantly improve soil bacterial community characteristic and nutrient contents - Cheng Xu; Xiaopeng Liu; Zhuangzhuang Qian; Tao Yang; Bo Wang; Xiaomin Ge; Luozhong Tang (Applied Soil Ecology, 2025)

White Spot Syndrome Virus: A Detailed Review of Early Infection Events, Structural Protein Trafficking, and Innate Immune Evasion - Ling‐Ke Liu; Shan‐Shan Jing; Hai‐Peng Liu (Reviews in Aquaculture, 2025)
White spot syndrome virus (WSSV), the highly pathogenic double‐stranded DNA virus affecting crustaceans particularly shrimp and crayfish, has been causing severe diseases that result in significant economic losses in aquaculture. Despite various treatment efforts, current methods remain inadequate in effectively controlling the onset and transmission of the disease, underscoring the urgent need for innovative and efficient control and therapeutic strategies. Successful WSSV infection, along with the production of essential viral components, depends on continuous viral evolution, which serves as a key strategy to manipulate the host cellular environment, including host‐intrinsic factors and systems, as well as the antiviral immune responses. Research to date has primarily focused on WSSV structural characterization, initial cellular events following infection, functional analysis of viral components in regulating antiviral signaling pathways, and host cellular responses elicited by viral invasion. These studies shed light on critical pathogenic processes, including viral entry and intracellular transport events, trafficking of expressed viral structural proteins, and immune evasion mechanisms driven by virus‐host interaction. This review provides a comprehensive summary of recent progress in the development of WSSV infection cell models and elucidation of innate immune evasion strategies driven by virus‐host interplay. By consolidating current knowledge, it aims to enhance our understanding of WSSV pathogenesis and lay a solid foundation for development of innovative therapeutic approaches.

Microbial community composition and interactions in saline biocrusts: Insights into cyanobacterial inoculation for soil restoration - Wenfei Li; Peng Liu; Yadong Jin; Lu Chen; Mingquan Zhao; Li Wu; Shubin Lan (Applied Soil Ecology, 2025)

Grazing exclusion changes the complexity and stability but not the α-diversity of the microbial community in a desert steppe - Fengqin Yuan; Xuebao Xu; Zhenpeng Liu; Rula Sa; Chongzhi Sun; Jia Liu; Na Li; Yujuan Zhang; Tongrui Zhang; Tingting Xing; Jie Ren; Shiming Tang; et al. (Applied Soil Ecology, 2025)

Important but ignored: Research progress on crab foraging behaviour and its implications for aquaculture - Dapeng Liu; Boshan Zhu; Xiaoshou Liu; Fang Wang (Reviews in Aquaculture, 2024)
Crab fisheries play a crucial role in global fishery economics, but they heavily rely on wild catches. With the decline and exploratory limits of wild populations, expanding the scale and production of aquaculture becomes vital for the sustainability of crab fisheries. The development of crab aquaculture encounters significant dietary challenges, stemming from suboptimal formulated feeds and inefficient feeding management. Leveraging insights from crab foraging behaviours offers a promising solution to these issues; however, progress is hindered by a lack of comprehensive behavioural data and the underappreciation of these insights in aquaculture. To bridge this gap, we systematically examine the progress in studies of crab foraging behaviour, analysing the influences of predators, prey, and environmental characteristics, and discuss possibilities for future research and development in the field by combining these findings with the demands of aquaculture. This review identifies a discrepancy in research focus, with inadequate emphasis on the major cultured species and their behavioural responses to factors limiting aquaculture productivity, aiming to enhance our comprehension of crab foraging behaviour and facilitate growth in the crab industry.

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

Environmental controls on carbon fluxes in an urban forest in the Megalopolis of Beijing, 2012-2020 - Peng Liu; Tianshan Zha; Feng Zhang; Xin Jia; Charles P.-A. Bourque; Yun Tian; Yujie Bai; Ruizhi Yang; Xinhao Li; Haiqun Yu; Jing Xie; Jun Mao (Agricultural and Forest Meteorology, 2023)

Multi-year trends and interannual variation in ecosystem resource use efficiencies in a young mixedwood plantation in northern China - Chuan Jin; Tianshan Zha; Charles P.-A. Bourque; Peng Liu; Xin Jia; Feng Zhang; Haiqun Yu; Yun Tian; Xinhao Li; Xiaoyu Kang; Xiaonan Guo; Ning Wang (Agricultural and Forest Meteorology, 2023)